The TaRL Approach as a Driver of Technological Innovation in Mathematics Learning in Senior High Schools/Vocational High Schools - Noor Izza Kamila; Ilma Sururina; Puteri Rakhma; Idrus Affandi; Ayu Tiaraningsih; Neneng Aminah; Dede Endang Mascita (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2025)
The Industrial Revolution 4.0 demands that the world of education adapt to technological developments. In mathematics learning in high schools/vocational schools, the use of technology and appropriate learning approaches to improve the quality of education is very important. The Teaching at the Right Level (TaRL) approach, which adjusts teaching to the level of individual student ability, is considered relevant to create a more effective and efficient learning process. This study aims to examine the role of the TaRL approach as a driver of technological innovation in mathematics learning at the high school/vocational school level. The method used is a literature review by reviewing 10 articles related to the research topic. The results and discussion of the study explain that the integration of TaRL with technology, such as GeoGebra software, Google Sites, and other digital devices can improve students' understanding of mathematical concepts, critical thinking skills, and learning motivation. This approach also supports inclusive learning that is relevant to the needs of the digital era. However, on the other hand, there are challenges that arise including limited teacher competence in the use of technology and gaps in access to digital infrastructure. This can affect the effectiveness of the implementation of the technology-based TaRL approach. Thus, intensive training for educators and increased access to infrastructure are needed to support optimal implementation. This approach is expected to inspire educators in creating more adaptive, innovative, and future-oriented learning.